PENGARUH BRAND IMAGE PRODUK SYARIAH TERHADAP LOYALITAS NASABAH PERBANKAN ( KasusBank Rakyat Indonesia Syariah Pekanbaru ) - Brando, Alberto; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Brand image to make belief - representing all important esensi to develop build a success business – do not only from in perpective all dealer but also from client. Brand have to can bear desire of client and than if that have been done/conducted to be expected by a client become loyal to bank defance of all client of exist in generally will be more profit compared to by a client commutation. Expense to draw new client can fivefold bigger than at expense maintain client there is. Brand Image of bank of BRI Syariah have just good enough only felt less. Loyalitas of Client of have a notion that loyalitas represent komitmen of client for the usage repeatedly an product or service in a period of/to will come with same brand. Lack of loyalitas of client at bank BRI Syariah also can be seen from less be its his enthusiastic is client to event done/conducted by bank.This research is done/conducted in BRI Syariah, Jl. Arifin Ahmad Town. Pekanbaru. As for reason chosen BRI SYariah that to measure storey level of loyalitas of client and the happening of percentage of descend sum up client. target of this Research is done/conducted to know influence of brand image to client loyality.In this research is methodologies used by is quantitative and descriptive with program SPSS, where sample used by that is client and as source of information is party of HRD and Manager marketing. To determine sampel use formula Slovin, method of sampling by accidental sampling. Technics of data collecting of through, observation and quesioner.From result analys data covering validity test, reabilitas, and linear regresi modestly, brand image to client loyality. Each owning indicator which each other be interconnected and have an effect on positive to loyality in BRI Syariah Pekanbaru.Keyword: Brand Image and Client Loyality